4H-1,2,6-Thiadiazin-4-one-containing small molecule donors and additive effects on their performance in solution-processed organic solar cells - Hermerschmidt, Felix; Kalogirou, Andreas S.; Min, Jie; Zissimou, Georgia A.; Tuladhar, Sachetan M.; Ameri, Tayebeh; Faber, Hendrik; Itskos, Grigorios; Choulis, Stelios A.; Anthopoulos, Thomas D.; Bradley, Donal D. C.; Nelson, Jenny; et al. (Journal of Materials Chemistry C, 2015)
The optical, electrochemical, morphological and transport properties of a series of thiadiazinone (acceptor) and (thienyl)carbazoles (donor) containing π-extended donor-acceptor-donors (D-A-D) are presented. Systematic variations in the number of the thienyl units, the choice of branched or straight alkyl side chains and the use of a processing additive demonstrate their use as electron donors in bulk heterojunction solar cells blended with fullerene acceptors. The best power conversion efficiency (PCE) of 2.7% is achieved by adding to the D-A-D 3:fullerene blend a polydimethylsiloxane (PDMS) additive, that improves the morphology and doubles the hole mobility within the D-A-D:fullerene blend.